Adverb of Time Analysis on Novel “After the Ending” By Lindsey Fairleigh - Amanda Ariffani Sholikha; Lilia Indriani (STAIN Sultan Abdurrahman Kepulauan Riau, 2021)
Reading is an activity that EFL students always do. They can read a textbook or even a novel in their leisure time. Reading activity read the paragraph, sentence, and text. However, as EFL students, they must understand what are they read for study and improve their knowledge about the structural grammar and the function of the words by reading kind of books like a novel. In grammar, there is a term part of speech. Part of speech is divided into five parts: Noun, Verb, Adjective, Adverb, and Preposition. In this time, students can focus on Adverb, mainly Adverb of time, to know and understand about Adverb of time and function in the novel's story already read. This article is descriptive qualitative research that aims to identify Adverbs of time from the novel After the Ending by Lindsey Fairleigh. Adverbs of time may appear in several sentences in this novel. This study shows how many Adverbs of time appear in the story and the function of Adverb of time in the story.